Multislice Computed Tomography Overestimates Superior Semicircular Canal Dehiscence Syndrome. (October 2013) - Re, Massimo; Gioacchini, Federico Maria; Salvolini, Ugo; Totaro, Anna Maria; Santarelli, Andrea; Mallardi, Vito; Magliulo, Giuseppe
Objectives: We assessed the prevalence of superior semicircular canal dehiscence (SSCD) through examination of ultrahigh-resolution computed tomography (CT) scans of the temporal bone and attempted to verify the correspondence between a radiologic diagnosis of SSCD and clinical signs of SSCD syndrome. Methods: A prospective study was carried out on 191 consecutive patients who underwent temporal bone ultrahigh-resolution CT scans. Cases that matched the radiologic diagnosis of SSCD were subsequently referred for a comprehensive audiological evaluation that might enable a final diagnosis of SSCD syndrome. Results: Among the 191 patients, 17 had a radiologic diagnosis of SSCD, which was bilateral in 5 cases, for a total of 22 SSCD cases, with a prevalence rate of 5.8%. In 2 of the 17 patients, the audiological examination revealed signs and symptoms indicative of SSCD syndrome, with a total prevalence rate of 0.5%. Conclusions: Our data confirm that the radiologic diagnosis of SSCD, performed by mean thin-section CT scans reformatted in the plane of the superior semicircular canal, is not necessarily related to the clinical presentation of SSCD syndrome. Our study also showed a prevalence rate of SSCD syndrome that was similar to the prevalence of SSCD reported from studies of histologic specimens.